Develop a preliminary core germplasm with the novel polymorphism EST-SSRs derived from three transcriptomes of colored calla lily (Zantedeschia hybrida) - Wang, Yi; Yang, Tuo; Wang, Xue; Sun, Xuan; Liu, Hongyan; Wang, Di; Wang, Huanxiao; Zhang, Guojun; Li, Yanbing; Wang, Xian; Wei, Zunzheng (Frontiers in Plant Science, 2023)
The development of high-throughput sequencing technology has made it possible to develop molecular markers such as EST-SSR from transcriptome sequences in non-model plants such as bulbous flowers. However, the EST-SSR markers that have been developed are weakly validated and low polymorphic due to the short read size and poor quality of the assembled sequences. This study therefore used the CandiSSR pipeline to identify 550 potential polymorphic SSR loci among 487 homologous unigenes based on the transcriptomic sequences of three varieties of colored calla lily, and 460 of these loci with appropriate flanking sequences were suitable for primer pairs design. A further validation with 200 randomly selected EST-SSRs demonstrated an increase of more than 30% and 100% in amplification validity and polymorphism, respectively, in comparison with our previous study. In addition, since most of the current varieties of colored calla lily are hybridized from a few species, which have low genetic diversity, we subsequently identified primary core germplasm for 160 colored calla lily accessions using the aforementioned 40 polymorphic EST-SSRs. It was concluded that the core germplasm containing 42 accessions derived from the M strategy incorporated into the software Power Core was the most representative of all 160 original germplasm, as evidenced by the preservation of 100% of the EST-SSR variation, with a higher level of genetic diversity and heterogeneity (Nei = 0.40, I = 0.66, PIC = 0.43). This study provides a practical example of polymorphism EST-SSR markers developed from multiple transcriptomes for non-model plants. A future breeding program for colored calla lily will also benefit from the core germplasm defined by those molecular markers.